2017
DOI: 10.5414/alx01287e
|View full text |Cite
|
Sign up to set email alerts
|

Complementary alternative medicine (CAM) and atopic eczema

Abstract: Abstract. There is a substantial and growing interest in complementary and alternative medicine (CAM) in the general population. This paper aims to answer in how far patients with atopic eczema use CAM and which techniques. Furthermore the evidence basis on the efficacy of CAM in the use for atopic eczema should be reviewed. For that purpose randomized controlled trials (RCT) were searched systematically. In Germany about 46% of the general population and up to 51% of inpatients with eczema use CAM. Acupunctur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 61 publications
0
12
1
Order By: Relevance
“…Some patients used supplement alternative therapy to avoid using corticosteroids; however, the evidence basis for this treatment is limited. We previously reported that children's experiences with CAMs for AD treatment were associated with more severe AD, higher IgE sensitization, lower quality of life of the caregiver, and higher steroid phobia tendency of the caregiver than those that did not use CAMs 37,38 . Providing appropriate information about corticosteroid therapy for AD may remove patients' anxiety, fear, and misunderstanding of steroids and may change their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients used supplement alternative therapy to avoid using corticosteroids; however, the evidence basis for this treatment is limited. We previously reported that children's experiences with CAMs for AD treatment were associated with more severe AD, higher IgE sensitization, lower quality of life of the caregiver, and higher steroid phobia tendency of the caregiver than those that did not use CAMs 37,38 . Providing appropriate information about corticosteroid therapy for AD may remove patients' anxiety, fear, and misunderstanding of steroids and may change their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In another randomized, doubleblinded, placebo-controlled trial with 45 eczema patients, SCORAD assessment showed improvement in the patients who ingested vitamin E supplements [22]. In a recent Italian study, 46% of patients in the vitamin E group showed improvement compared to only 2% of patients in the placebo group [27]. A meta-analysis concluded that vitamin E improved the SCORAD Indexin eczema patients [28].…”
Section: Vitamin Ementioning
confidence: 97%
“…As a result, there is increasing interest in the use of complementary and integrative medicine treatments, especially natural bioactive substances made from plant extracts, in AD patients. 10,11 Centella asiatica, widely known as gotu kola, is a traditional medicinal herb that has been used to have pharmacological benefits for many diseases such as varicose ulcers, diarrhoea, fever, and eczema. The most significant bioactive triterpenes, asiaticoside, madecassoside.…”
Section: Introductionmentioning
confidence: 99%